Design and Analysis of a Rotor for a 22 kW Transversally Laminated Anisotropic Synchronous Reluctance Motor - Ozdil, Ali; Uzun, Yunus (Elektronika ir Elektrotechnika, 2021)
Substantial increase in energy consumption in all around the world has led to researchers to need to produce electrical machines with high energy efficiency since majority of energy has been consumed at industry, especially by electrical machines. Among electrical machines, the Synchronous Reluctance Machines (SynRMs) have been preferred to investigate in recent years due to lack of Induction Machines (IMs) in terms of efficiency and high price of the Permanent Magnet Synchronous Machines (PMSMs). In this study, the Finite Element Analysis (FEA) showing the effects of phase angle of current, number of flux barriers, starting diameter of flux barriers, and ribs on machine performance of 22 kW Transversally Laminated Anisotropic (TLA)-SynRM with distributed winding have been carried out in ANSYS Electronics. The design is based on creating a novel rotor considering these rotor parameters since the utilized SynRM consists of same stator with same sized 22 kW IM. The performance of the machine has been investigated through torque, torque ripple, efficiency, saliency, and power factor. Moreover, the effect of the phase angle of the current on the machine performance and the comparison of the 22 kW-SynRM with the same sized and powered IM and with a different SynRM have been carried out in this study. This study has concluded that although the novel SynRM has high torque ripple values, it is better than the IM due to lack of copper losses of rotor and the previously utilized SynRM considering their efficiency classes. The efficiency class of novel SynRM is IE4, whereas that for utilized IM and previously created SynRM are IE1 and IE3, respectively.